(untitled) (Bangladesh Journal of Agricultural Research, 2013)
Thirty genotypes collected from India, Burma, and Bangladesh were studied for thier genetic divergence using Mahalanobi´s D2 and Rao´s canonical analysis. Altogether five clusters were formed. The pattern of distribution of genotypes into five clusters was random demonstrating that the geographical isolation might not be the only factor causing genetic diversity. Leaf length and sulfur content contributed predominantly towards genetic divergence. Cluster III recorded the highest means for number of leaves per plant, leaf length, bulb length, plant height, and bulb yield. The results obtained from D2 analysis were confirmed by canonical analysis. The genotype G12 showed highest mean performance for moisture content (88.49%), G13 for leaf length (39.06 cm), G15 for neck diameter at vegetative stage (11.21 mm), bulb length (49.09 mm), plant height (64.82 cm) and as well as bulb yield (13.17 t/ha), G19 for percent sulfur content (0.84) and G26 for number of leaves per plant (12), respectively. DOI: http://dx.doi.org/10.3329/bjar.v37i4.14375 Bangladesh J. Agril. Res. 37(4): 573-582, December 2012